2008
DOI: 10.1016/j.ijgo.2008.11.036
|View full text |Cite
|
Sign up to set email alerts
|

Depression among Nigerian women following pregnancy loss

Abstract: Most Nigerian women suffer some level of depression following pregnancy loss, with no living children and losses after 20 weeks being the most significant risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 21 publications
(24 reference statements)
2
22
0
2
Order By: Relevance
“…A three-fold increased risk of high depressive symptoms was found for women experiencing an early post-neonatal infant death between one to three months after the delivery after adjusting for important confounders, relative to women not experiencing fetal/infant death. Prior research suggests that longer time with the child may confer a higher risk of depressive symptoms; for example, Nigerian women with late pregnancy loss were more likely to have depressive symptoms than those with a fetal loss early in pregnancy [8]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A three-fold increased risk of high depressive symptoms was found for women experiencing an early post-neonatal infant death between one to three months after the delivery after adjusting for important confounders, relative to women not experiencing fetal/infant death. Prior research suggests that longer time with the child may confer a higher risk of depressive symptoms; for example, Nigerian women with late pregnancy loss were more likely to have depressive symptoms than those with a fetal loss early in pregnancy [8]. …”
Section: Discussionmentioning
confidence: 99%
“…Little is known about depressive symptoms following such adverse experiences in Bangladesh, despite the fact that these rates are over five times higher than in high income countries [6, 7]. Reporting problems, small sample size, hospital-based samples, and limited adjustment for confounders constrain research on pregnancy loss and maternal depression in LAMI countries [812]. Composite variables are often used to address lack of power, such that stillbirths are combined with neonatal loss, limiting our understanding of the mental health impact of loss of a live born infant relative to a stillbirth.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the more the women considered they were being supported, the less likely they were to experience maternal anxiety, which was associated with a lower level of depression. Obi et al (2009) determined the level of depression in Nigerian women following spontaneous pregnancy loss and the coping strategies implemented. They concluded that most Nigerian women suffered some level of depression following pregnancy loss, with no living children and losses.…”
Section: Introductionmentioning
confidence: 99%
“…[6,7] Düşüğün fiziksel semptomları olan vajinal kanama, kramp ve ağrının başlaması ile birlikte kadında kaygı, korku, çaresizlik, kontrol kaybı, intihar, anksiyete ve depresif belirtiler gibi psikolojik semptomlar da görülebilmektedir. [4,[8][9][10][11] Yapılan çalışmalarda, düşüğe bağlı anksiyete semptomlarının %30-50 arasında değiştiği, depresyon belirtilerinin ise %10-55 oranında görüldüğü, bu belirtilerin ise düşükten hemen sonra ortaya çıktığı ve altı ay ile bir yıl kadar devam ettiği bildirilmiştir. [7,9,[11][12][13] Düşük nedeni ile yaşanan kayıp, kadınların yas sürecini yaşamasına da yol açmaktadır.…”
unclassified
“…[4,[8][9][10][11] Yapılan çalışmalarda, düşüğe bağlı anksiyete semptomlarının %30-50 arasında değiştiği, depresyon belirtilerinin ise %10-55 oranında görüldüğü, bu belirtilerin ise düşükten hemen sonra ortaya çıktığı ve altı ay ile bir yıl kadar devam ettiği bildirilmiştir. [7,9,[11][12][13] Düşük nedeni ile yaşanan kayıp, kadınların yas sürecini yaşamasına da yol açmaktadır. [14,15] Yas süreci ile ilgili yapılan çalışmalarda düşük yapan kadınların %40'nın kısa süre içerisinde hemen yas dönemine girdikleri belirlenmiştir.…”
unclassified